Cross-delisting, financial constraints and investment sensitivities - Loureiro, Gilberto (2015)
We investigate the impact of cross-delisting on firms’ financial constraints and investment sensitivities. We find that firms that cross-delisted from a U.S. stock exchange face stronger post-delisting financial constraints than their cross-listed counterparts, as measured by investment-to-cash flow sensitivity. Following a delisting, the sensitivity of investment-to-cash flow increases significantly and firms also tend to save more cash out of cash flows. Moreover, this increase appears to be primarily driven by informational frictions that constrain access to external financing. We document that information asymmetry problems are stronger for firms from countries with weaker shareholders protection and for firms from less developed capital markets.